Perancangan Sistem Monitoring Suhu Pada Ruangan Berbasis Arduino Dan Sensor DHT Dengan Dashboard Web - Depi Itnafia; Sindi Dewi Oktafiani; Dimas Ardian; Muhammad Abbas Jailani Syhafitri (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
Advancements in Internet of Things (IoT) technology enable automated, real-time environmental monitoring. Room temperature is a critical environmental parameter to monitor, as it affects both comfort and the performance of devices within the space. This study aims to design an Arduino- and DHT-sensor-based room temperature monitoring system connected to a web dashboard. The research employs a prototyping methodology, encompassing design, prototype construction, testing, and system evaluation. A DHT sensor detects room temperature; the data is then processed by an Arduino and transmitted to a web-based system for display on a dashboard, allowing for real-time monitoring. The study resulted in a system capable of accurately presenting room temperature information that is easily accessible via a web dashboard. This system optimizes the room temperature monitoring process, saves time, and enables monitoring without the need for physical presence at the location.